Antibacterial Activity Of Freshwater Lobster Shells (Cherax quadricarinatus) Against Escherichia coli - Hafizha, Putri; Ridwanto, Ridwanto; Daulay, Anny Sartika; Nasution, Haris Munandar (Pustaka Media Publishing, 2024)
People still do not utilize freshwater lobster (Cherax quadricarinatus) shells optimally, even though the chitin compound contained in this waste can be modified into chitosan through chemical reactions. Chitosan obtained from freshwater lobster shells can be used as an antibacterial. This study aims to test the antibacterial activity of chitosan from freshwater lobster shell waste against Escherichia coli bacteria. Making chitosan is carried out through three processes, namely, demineralization, deproteination, and deacetylation stages. Then, characterization of the chitosan is carried out, which includes water content, ash content, yield, and solubility. The research results showed that the chitosan obtained in this study was 43.96%, and the degree of deacetylation value of freshwater lobster shell chitosan was 75.11%. Chitosan with a concentration of 0.3, 0.5, 0.7, and 0.9% provides an inhibition zone of 13.5, 15.9, 16.8, and 17.2 mm, respectively, against Escherichia coli. Thus, a concentration of 0.9% chitosan from freshwater lobster shells has better antibacterial activity and is categorized as having strong inhibitory power.